The Implementation of Child-Friendly School to Fulfill Children’s Rights and Prevent Violence Against Children - Tusriyanto Tusriyanto; Aria Septi Anggaira; Anita Lisdiana; Atik Purwasih; Karsiwan Karsiwan; Nina Ikhwati Wahidah; Nikki Tri Sakung; Ike Festiana; Iskandar Iskandar (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to describe the efforts made by teachers in fulfilling the children’s rights and preventing of violence against children through child-friendly school policy in the Islamic elementary schools. This research was qualitative descriptive research, and the research subjects were of teachers and principals of 7 several Islamic elementary schools located in Lampung Province (Metro, East Lampung, Pringsewu, and Tanggamus). The sampling technique was purposive random sampling, while the data were collection through interviews, observation, documentation, and literature study. The results of this research showed that: 1) providing protection2) providing consultation rooms, counseling guidance to parents and students, 3) doing fun activities 4) providing facilities that ensure the safety of learners 5) socializing, opening communication 6) providing good example  7) supervision, and mentoring  8) create regulations that guarantee the rights and safety of learners both physical and psychological, 9) attach posters about child-friendly education, and 10) Give a admonition to teachers who commit acts of Violence toward students. The implementation of child-friendly learning in madrasas during the covid-19 pandemic has been carried out well online, offline, and a home visit.